Examining Perceived Risk and Behavioral Intention in the Context of COVID-19 Pandemic - I Gusti Lanang Agung Kharisma Wibhisono; Ummi Salamah (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
An individual’s subjective assessment of the probability of negative consequences could influence the willingness to perform certain behaviors. Previous literature had identified socio-psychological factors that influence behavioral intention in various contexts. However, their influence on perceived risk and behavioral intention in a pandemic is rarely discussed. Using quantitative approach, empirical data were obtained through a survey of Denpasar citizens aged 17-30 (n=212) and analyzed using the PLS-SEM method. The result suggests that perceived risk could be influenced by interpersonal discussion, trust in institutions, and information-seeking ability. Meanwhile, efficacy belief and perceived risk could influence the intention to wear masks. On the other hand, media and internet exposure do not show significant influence on perceived risk.